The Impact of Gender and Early Delinquency on Reoffending: A Life History Perspective. Issue 2 (2nd April 2016) - McConaghy, Megan; Levy, Marissa P.
Abstract: In New Jersey, conversations within a statewide antiviolence initiative stimulated the idea to begin interviewing local repeat offenders to uncover the root of their criminal trajectories. Capturing the life histories of recidivists provides a rich understanding of how these individuals entered and remained in a criminal lifestyle. Employing qualitative methods, 20 men and women were interviewed in a local county jail and asked to describe numerous aspects of their lives that may have contributed to their criminal outcome. Similarities and differences are described between and among the men and women.